Effect of a Single Preoperative Dose of Oral Antibiotic to Reduce the Incidence of Surgical Site Infection Following Below-knee Dermatological Flap and Graft Repair - Helena Rosengren; Clare F. Heal; Petra G. Buttner (Mattioli1885, 2019)
Background: Surgical site infection (SSI) rates for below-knee dermatological surgery are unacceptably high, particularly following complex flap and graft closures. The role of antibiotic prophylaxis for these surgical cases is uncertain. Objective: To determine whether SSI following complex dermatological closures on the leg could be reduced by antibiotic prophylaxis administered as a single oral preoperative dose. Methods: A total of 115 participants were randomized to 2 g of oral cephalexin or placebo 40-60 minutes prior to surgical incision in a prospective, randomized, double-blind, placebo-controlled trial at a primary care skin cancer clinic in North Queensland, Australia. Results: Overall 17/55 (30.9%) controls and 14/55 (25.5%) intervention participants developed infection (P = 0.525). There was no difference between the study groups in adverse symptoms that could be attributed to high-dose antibiotic administration (P = 1). Conclusion: A single oral 2-g dose of cephalexin given before complex below-knee dermatological closure did not reduce SSI.